Regulating Gene Editing in the Wild: Building Regulatory Capacity to Incorporate Deliberative Democracy - Maschke, Karen J. (The Hastings Center report, 2021)
The release of genetically engineered organisms into the shared environment raises scientific, ethical, and societal issues. Using some form of democratic deliberation to provide the public with a voice on the policies that govern these technologies is important, but there has not been enough attention to how we should connect public deliberation to the existing regulatory process. Drawing on lessons from previous public deliberative efforts by U.S. federal agencies, we identify several practical issues that will need to be addressed if relevant federal agencies are to undertake public deliberative activities to inform decision-making about gene editing in the wild. We argue that, while agencies may have institutional capacity to undertake public deliberative activities, there may not be sufficient political support for them to do so. Advocates of public deliberation need to make a stronger case to Congress about why federal agencies should be encouraged and supported to conduct public deliberations.